Kalimat Bahasa Indonesia dalam Tulisan Argumentasi Siswa Kelas X SMAN 3 Kota Solok - Mihartati, Isra; Ngusman, Ngusman; Emidar, Emidar (Universitas Negeri Padang, 2012)
The purpose of this study was to describe (1) the accuracy of the sentence in an argument paper of Class X students of SMAN 3 City Solok terms of proper reasoning, (2) the accuracy of the sentence in an argument paper of Class X students of SMAN 3 City Solok terms of precise language, and (3) the accuracy sentence in an argument paper of Class X students of SMAN 3 City Solok terms of proper reasoning and precise language. The data in this study are sentences in an argument writing class X SMAN 3 Solok. Data collected by the method refer to the written test techniques. The findings in this study as follows: (1) the accuracy of the sentence in an argument essay class X SMAN 3 Solok of reasoning as very precise terms (87.84%), (2) the accuracy of the sentence in terms of linguistic relatively less (26.01% ), (3) the accuracy of a sentence based on indicators of the accuracy and precision of language reasoning as very less (21.28%)